Analisis Kelayakan Finansial dan Non Finansial pada Usaha Kopra di Desa Siduwonge Kecamatan Randangan Kabupaten Pohuwato - Yuriko Boekoesoe; Amelia Murtisari; Yenni Umar (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
The purpose of this study were: 1). To determine whether the copra business financially worth the effort in the Village District of Randangan Siduwonge Pohuwato. 2). To determine whether the effort is worth the effort copra nonfinancial Siduwonge Village District of Randangan Pohuwato. This study was conducted in May to July. This type of research is survey research. The data obtained in this study is that the data in the form of primary and secondary data. Sampling will be done against the 30 respondents using purposive sampling. The analysis used is the financial analysis of the Net Present Value (NPV), Internal Rate of Return (IRR), Gross B / C Ratio, Net B / C Ratio and Payback Period. The results showed 1). Financially copra business in the Village District of Randangan Pohuwato Siduwonge worth the effort with 9.2 Million NPV, IRR (20.11%), Gross B / C ratio (1.27), Net B / C ratio (3.38 ) and payback period of 7 years 6 months. 2). In non-financial businesses in the village copra Siduwonge District of Randangan Pohuwato divided on several aspects which are as follows: a). Aspects of the Market. In a marketing system for businesses in the Village Siduwonge copra, farmers sell directly to buyers who typically have long subscription. Where the buyer directly come to the farmers who sell the copra. b). Technical Aspects. In this technical aspect of the farmers in the village siduwonge almost all have their own land as many as 25 people, but there are also some who rent land that is 5 people. c). Management aspects. In the management aspect of the planning is done before the process of harvesting coconuts into copra to be produced, the farmers in the village siduwonge not incorporated in the organization and for the direction and supervision in accordance with the land held by the copra farmers and for supervision also aims to work performed by farm workers in accordance with a predetermined agreement.